2020
DOI: 10.1021/acs.analchem.0c01971
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Structural Characterization of Individual Viral Particles Using Atomic Force Microscopy Infrared Spectroscopy (AFM-IR) and Tip-Enhanced Raman Spectroscopy (TERS)

Abstract: Viruses are infections species that infect a large spectrum of living systems. Although displaying a wide variety of shapes and sizes, they are all composed of nucleic acid encapsulated into a protein capsid. After virions enter the host cell, they replicate to produce multiple copies of themselves. They then lyse the host, releasing virions to infect new cells. The high proliferation rate of viruses is the underlying cause of their fast transmission among living species. Although many viruses are harmless, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 49 publications
1
83
0
Order By: Relevance
“…Masterson et al (2020) proposed a method of "liquid biopsy" based on the evaluation of microRNA of cancers in plasma through surface-enhanced Raman spectroscopy (SERS) and plasmon-enhanced fluorescence (PEF), a method that could be expanded to the diagnosis of COVID-19 [25]. Also, Dou et al (2020) showed that viruses could be identified in a label-free way by tipenhanced Raman spectroscopy (TERS), by revealing protein secondary structure and amino acid composition of the virus surface [26]. Carvalho and Nogueira (2020) suggested in a "letter to the editor" that the vibrational techniques such as Raman and Fourier-transform infrared (FT-IR) spectroscopies could address the challenges for early and fast diagnosis of COVID-19 [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Masterson et al (2020) proposed a method of "liquid biopsy" based on the evaluation of microRNA of cancers in plasma through surface-enhanced Raman spectroscopy (SERS) and plasmon-enhanced fluorescence (PEF), a method that could be expanded to the diagnosis of COVID-19 [25]. Also, Dou et al (2020) showed that viruses could be identified in a label-free way by tipenhanced Raman spectroscopy (TERS), by revealing protein secondary structure and amino acid composition of the virus surface [26]. Carvalho and Nogueira (2020) suggested in a "letter to the editor" that the vibrational techniques such as Raman and Fourier-transform infrared (FT-IR) spectroscopies could address the challenges for early and fast diagnosis of COVID-19 [27].…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 10, 2021. ; https://doi.org/10.1101/2021.08.09.21261798 doi: medRxiv preprint Also, Dou et al (2020) showed that viruses could be identified in a label-free way by tipenhanced Raman spectroscopy (TERS), by revealing protein secondary structure and amino acid composition of the virus surface [26]. Carvalho and Nogueira (2020) suggested in a "letter to the editor" that the vibrational techniques such as Raman and Fourier-transform infrared (FT-IR) spectroscopies could address the challenges for early and fast diagnosis of COVID-19 [27].…”
Section: Introductionmentioning
confidence: 99%
“…A novel detecting method, single-cell Raman spectroscopy (scRS) coupled with one-dimensional convolutional neural networks (1DCNN) was explored to identify individual marine microorganisms quickly and accurately [163]. Moreover, combined microscopy-infrared (AFM-IR) spectroscopy and tip-enhanced Raman spectroscopy (TERS) provided a novel and automated approach to identify the structure of viruses [164].…”
Section: Developing Technologies For Structure Characterizationmentioning
confidence: 99%
“…Thus, it needs to be further validated with more extended experiments and other potential methods. For example, AFM-IR and TERS [49][50][51] could be a useful method, and molecular dynamics simulation (MS) will provide more detailed structure compositions. In addition, the microstructure of hardened cement paste is highly dependent on the cement type [52], service environment [53,54], such as blended cement [55], and clinker composition [56]-the results would need to be further evaluated.…”
Section: Supplement For the Microstructure Of Hydrated C 3 Smentioning
confidence: 99%